Brittle culm 3, encoding a cellulose synthase subunit 5, is required for cell wall biosynthesis in barley (Hordeum vulgare L.) - Guo, Baojian; Huang, Xinyu; Qi, Jiang; Sun, Hongwei; Lv, Chao; Wang, Feifei; Zhu, Juan; Xu, Rugen (Frontiers in Plant Science, 2022)
The cell wall plays an important role in plant mechanical strength. Cellulose is the major component of plant cell walls and provides the most abundant renewable biomass resource for biofuels on earth. Mutational analysis showed that cellulose synthase (CESA) genes are critical in cell wall biosynthesis in cereal crops like rice. However, their role has not been fully elucidated in barley. In this study, we isolated a brittle culm mutant brittle culm 3 (bc3) derived from Yangnongpi 5 ethyl methanesulfonate (EMS) mutagenesis in barley. The bc3 mutants exhibited reduced mechanical strength of the culms due to impaired thickening of the sclerenchyma cell wall and reduced cellulose and hemicellulose content in the culms. Genetic analysis and map-based cloning revealed that the bc3 mutant was controlled by a single recessive gene and harbored a point mutation in the HvCESA5 gene, generating a premature stop codon near the N-terminal of the protein. Quantitative real-time PCR (qRT-PCR) analysis showed that the HvCESA5 gene is predominantly expressed in the culms and co-expressed with HvCESA4 and HvCESA8, consistent with the brittle culm phenotype of the bc3 mutant. These results indicate that the truncated HvCESA5 affects cell wall biosynthesis leading to a brittle culm phenotype. Our findings provide evidence for the important role of HvCESA5 in cell wall biosynthesis pathway and could be a potential target to modify cell wall in barley.